HUBUNGAN PERSEPSI PEMBELAJARAN DARING TERHADAP TINGKAT PROKRASTINASI MAHASISWA - Salsabilla, Zahwa Ayunda; Bayhakki, Bayhakki; Woferst, Rismadefi (Coping: Community of Publishing in Nursing; Vol 10 No 4 (2022): Agustus 2022DO - 10.24843/coping.2022.v10.i04.p15, 2022)
Perception is a stage of work by one of the five senses so that an understanding is obtained. Increasing the role and activity of students for the success of online lectures is strongly influenced by perceptions. This perception will later shape students to be able to carry out online lecture activities well and enthusiastically, including one of them in self-regulation, managing or managing time. Students' perceptions of online learning are related to their behavior, one of which is doing academic procrastination behavior (procrastination behavior).This study aims to determine the correlation between students' perceptions of online learning and students' procrastination level in Nursing students at Riau University. This study used a descriptive correlational design with a cross-sectional approach. The research sample was 242 respondents using a simple random sampling technique. The analysis used univariate analysis to see the frequency distribution and bivariate analysis using the chi-square test. The measuring instrument used is an online learning perception questionnaire consisting of 12 statements that have been tested for validity with r count 0,461 - 0,745 > r table (0,444), and the academic procrastination questionnaire contains 16 statements that also have been tested for validity with r count 0,445 - 0,645 > r table (0,444). The questionnaires were distributed via a google form. The results showed that the majority of students had a positive perception of online learning (51,7%) and high academic procrastination behavior (56,2%). The results of the chi-square test show that there is a correlation between the perception of online learning and students' procrastination with a p-value (0,000) < alpha (0,05).  Academic procrastination in the Faculty of Nursing, University of Riau is in the high category. Students are expected to be more active and enthusiastic in participating in online lectures and increase understanding related to online learning so that they can operate and follow the online learning process comfortably and adequately to reduce academic procrastination behavior due to poor perceptions of online learning.